An evaluation of telehealth expansion in U.S. nursing homes. (9th November 2020) - Alexander, Gregory L; Powell, Kimberly R; Deroche, Chelsea B
Abstract: Objective: This research brief contains results from a national survey about telehealth use reported in a random sample of U.S. nursing homes. Methods and Materials: The sample includes nursing homes (N = 664) that completed surveys about information technology maturity, including telehealth use, beginning January 1, 2019, and ending August 4, 2020. A pre/post design was employed to examine differences in nursing home telehealth use for nursing homes completing surveys prior to and after telehealth expansion, on March 6, 2020. We calculated a cumulative telehealth score using survey data from 6 questions about extent of nursing home telehealth use (score range 0-42). We calculated proportions of nursing homes using telehealth and used logistic regression to look for differences in nursing homes based on organizational characteristics and odds ratios. Results: Significant relationships were found between nursing home characteristics and telehealth use, and specifically, larger metropolitan homes reported greater telehealth use. Ownership had little effect on telehealth use. Nursing homes postexpansion used telehealth applications for resident evaluation 11.24 times more ( P < .01) than did nursing homes pre-expansion. Discussion: Administrators completing our survey reported a wide range of telehealth use, including approximately 16% having no telehealth use and 5% having the maximum amount of telehealth use. Mean telehealth use scores reported by the majority of these nursing homes is on the lower end of the range. Conclusions: One solution for the current pandemic is to encourage the proliferation of telehealth with continued relaxed regulations, which can reduce isolation and preserve limited resources (eg, personal protective equipment) while maintaining proper distancing parameters.